2017
DOI: 10.14569/ijacsa.2017.080532
|View full text |Cite
|
Sign up to set email alerts
|

A Compendious Study of Online Payment Systems: Past Developments, Present Impact, and Future Considerations

Abstract: Abstract-The advent of e-commerce together with the growth of the Internet promoted the digitisation of the payment process with the provision of various online payment methods like electronic cash, debit cards, credit cards, contactless payment, mobile wallets, etc. Besides, the services provided by mobile payment are gaining popularity day-by-day and are showing a transition by advancing towards a propitious future of speculative prospects in conjunction with the technological innovations. This paper is aime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 15 publications
0
29
0
Order By: Relevance
“…The following facts were discovered after studying the previous authors' works [2,7,8,9,10,11] in the area of online transactions and frauds: There is certainly increase in digital transaction; identified types of online transactions; high risk of identity thefts in online digital transactions; loss of phone lead to loss of transaction or lead to fraud, as most of the transaction and confidential information is present with the users mobile; availability and confidentiality(unauthorized access) are also the issues of concern; proper end-to-end encryption credentials, etc., which enabled us to identify the key challenges of online transactions.…”
Section: Literature Reviewmentioning
confidence: 98%
“…The following facts were discovered after studying the previous authors' works [2,7,8,9,10,11] in the area of online transactions and frauds: There is certainly increase in digital transaction; identified types of online transactions; high risk of identity thefts in online digital transactions; loss of phone lead to loss of transaction or lead to fraud, as most of the transaction and confidential information is present with the users mobile; availability and confidentiality(unauthorized access) are also the issues of concern; proper end-to-end encryption credentials, etc., which enabled us to identify the key challenges of online transactions.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Similarly, another study undertaken in Malaysia in 2017 reported that security's methodology, technology and practice contribute to customers' acceptance of the security of the e-payment system. It was also discovered that three aspects of e-payment security influence customer acceptance: the security system's integrity, confidentiality and availability (Khan et al, 2017). There is thus adequate evidence to suggest that security has a major influence on accepting e-payment systems by the customers, hence hypothesis H1: H1.…”
Section: Customer Acceptance Of E-paymentmentioning
confidence: 99%
“…This enabled U.S commercial banks and its central treasury came out with an alternative to cheque payment. (Ul et al, 2017). Traditionally, banks have always sought media through which they would serve their clients more cost-effectively as well as increase the utility of their clientele.…”
Section: Introductionmentioning
confidence: 99%